Promise me [compact disc, unabridged] : how a sister's love launched the global movement to end breast cancer - Brinker, Nancy (Tantor Media, 2010)
Nancy Brinker, cancer advocate and former U.S. Ambassador to Hungary, chronicles her sister's struggles with breast cancer and eventual death. Here, Brinker reveals how her sister Susan Komen sparked the breast cancer awareness movement.